Nanowire-assisted Flow-through Electrode Enabling Electroporation Disinfection of Reclaimed Water - Huo, Zheng-Yang. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This Ph.D. book develops nanowire-assisted electroporation disinfection technology based on the flow-through porous electrode. The author presents pioneering results on theoretical modeling, experimental realization, and selected applications, showing the novel disinfection mechanism of electroporation guarantees an exceedingly low level of energy consumption. In this regard, three classes of novel dynamic behavior are investigated: (i) The developed nanowire-assisted flow-through electroporation disinfection technology enables great microbial disinfection performance with extremely low voltage (1V), which significantly reduce the formation potential of harmful disinfection by-products during the treatment process. (ii) The nanowire-assisted flow-through electroporation disinfection technology ensures no reactivation/regrowth of inactivated bacteria and meanwhile promotes the gradual death of damaged bacteria during the storage process. (iii) The application of high-frequency AC power supply (106 Hz) ensures the high microbial disinfection efficiency while suppressing the occurrence of electrochemical reactions and extending the electrode lifetime effectively.
Background -- Controlling Biological Risks in Reclaimed Water -- Preparation of Copper-oxide-nanowire-modified Foamed Copper Electrode -- The Disinfection Effect of Nanowire -- Effect of Cuprous Phosphide Nanowires -- Deposition of Polydopamine (PDA) Film on Nanowires -- Summary.
Keywords: Water; Hydrology; Environmental engineering; Biotechnology; Bioremediation; Refuse and refuse disposal; Electrochemistry; Nanotechnology; Water; Environmental Engineering/Biotechnology.; Waste Management/Waste Technology; Electrochemistry; Nanotechnology